MAPPING OF EROSION HAZARD VULNERABILITY BASED ON GIS AND USLE IN WAIRUTUNG WATERSHED, SALAHUTU DISTRICT, CENTRAL MALUKU REGENCY - Lasaiba, Mohammad Amin Lasaiba (JURNAL GEOGRAFI Geografi dan Pengajarannya, 2023)
This study aims to assess the erosion hazard level in the Wairutung Watershed. This study uses the results of overlaying land use maps, slope maps, and soil types maps to generate the Land unit, which is the unit of analysis. Done using a computer-based Geographic Information System (GIS) with the ArcGIS program integrated with the Universal Soil Loss Equation (USLE) model. The sum of the results of the rating of the parameters then determines the class of vulnerability. The results obtained from this study indicate the division of 4 categories of landslide hazards consisting of a very light course with an area of 2900,865 ha spread over land units with alluvial soil types. The medium type, with a total area of 3683.285 ha, is distributed over land units with podzolic soil types. Heavy type with a total area of 1458.367 ha and the whole place is spread over land units with podzolic and cytosol soil types. The erosion hazard level is hefty, with a total area of 421.97 ha, and is spread over land units with podzolic and cytosol soil types. Keywords: Erosion, Vulnerability, and USLE